Epidemiology of E. coli in Cystic Fibrosis Airways Demonstrates the Capacity for Persistent Infection but Not Patient-Patient Transmission - Izydorczyk, Conrad; Waddell, Barbara; Edwards, Brett D.; Greysson-Wong, Jasper; Surette, Michael G.; Somayaji, Ranjani; Rabin, Harvey R.; Conly, John M.; Church, Deirdre L.; Parkins, Michael D. (Frontiers in Microbiology, 2020)
Escherichia coli is frequently isolated from the respiratory secretions of cystic fibrosis (CF) patients yet is not considered a classical CF pathogen. Accordingly, little is known about the natural history of this organism in the CF airways, as well as the potential for patient-to-patient transmission. Patients attending the Calgary Adult CF Clinic between January 1983 and December 2016 with at least one E. coli-positive sputum culture were identified by retrospective review. Annual E. coli isolates from each patient were typed by pulsed-field gel electrophoresis (PFGE) and isolates belonging to shared pulsotypes were sequenced. Single nucleotide polymorphism (SNP) and phylogenetic analysis were used to investigate the natural history of E. coli infection and identify potential transmission events. Forty-five patients with E. coli-positive sputum cultures were identified. Most patients had a single infection episode with a single pulsotype, while replacement of an initial pulsotype with a second was observed in 3 patients. Twenty-four had E. coli recovered from their sputum more than once and 18 patients had persistent infections (E. coli carriage >6 months with 3 positive cultures). Shared pulsotypes corresponded to known extraintestinal pathogenic E. coli strains: ST-131, ST-73, and ST-1193. Phylogenetic relationships and SNP distances among isolates within shared pulsotypes were consistent with independent acquisition of E. coli by individual patients. Most recent common ancestor date estimates of isolates between patients were inconsistent with patient-to-patient transmission. E. coli infection in CF is a dynamic process that appears to be characterized by independent acquisition within our patient population and carriage of unique sets of strains over time by individual patients.